2015
DOI: 10.5194/bg-12-2077-2015
|View full text |Cite
|
Sign up to set email alerts
|

Methanotrophy within the water column of a large meromictic tropical lake (Lake Kivu, East Africa)

Abstract: Abstract. The permanently stratified Lake Kivu is one of the largest freshwater reservoirs of dissolved methane (CH 4 ) on Earth. Yet CH 4 emissions from its surface to the atmosphere have been estimated to be 2 orders of magnitude lower than the CH 4 upward flux to the mixed layer, suggesting that microbial CH 4 oxidation is an important process within the water column. A combination of natural abundance stable carbon isotope analysis (δ 13 C) of several carbon pools and 13 CH 4 -labelling experiments was car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 48 publications
5
48
0
1
Order By: Relevance
“…The present paper also complements the work of Morana et al (2015b) based on the same two-year sampling at Ishungu, which mainly focused on the biogeochemistry of organic matter.…”
Section: Introductionmentioning
confidence: 64%
“…The present paper also complements the work of Morana et al (2015b) based on the same two-year sampling at Ishungu, which mainly focused on the biogeochemistry of organic matter.…”
Section: Introductionmentioning
confidence: 64%
“…Such large isotopic depletion of the POC pool in the water column has been reported by Blees et al (2014), who measured δ 13 C-POC as low as −49 ‰ in Lake Lugano, and it was related to high methanotrophic activity. In Lake Kivu, CH 4 concentrations were found to decrease sharply with decreasing depth at the oxic-anoxic transition (Borges et al, 2011), and the dissolved CH 4 that reached the oxycline via turbulent diffusivity and vertical advection (Schmid et al, 2005) is known to be isotopically light, with a δ 13 C signature of approximately −60 ‰ (Pasche et al, 2011;Morana et al, 2015). Therefore, the vertical patterns in CH 4 concentrations and δ 13 C-POC values observed during this study suggest that a substantial part of CH 4 was consumed and incorporated into the microbial biomass in the oxycline.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the vertical patterns in CH 4 concentrations and δ 13 C-POC values observed during this study suggest that a substantial part of CH 4 was consumed and incorporated into the microbial biomass in the oxycline. Indeed, experiments carried out in Lake Kivu in February 2012 and September 2012 showed that microbial CH 4 oxidation was significant in the oxycline, and phospholipid fatty acid analysis revealed high abundance of methanotrophic bacteria of type I at the same depths (Morana et al, 2015). With es-timates of the isotope fractionation factor during microbial CH 4 oxidation (1.016, Morana et al, 2015), and of the δ 13 C-CH 4 at each sampling point, it is possible to estimate the theoretical δ 13 C signature of methanotrophic organisms at each depth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations